Experimental investigation of high replacement of cement by pumice in cement mortar: A mechanical, durability and microstructural study. (15th May 2022) - Rahman, Fayyaz; Adil, Waqas; Raheel, Muhammad; Saberian, Mohammad; Li, Jie; Maqsood, Tariq
Abstract: Pozzolanic materials have long been used to enhance the mechanical and durability properties of mortar and concrete. It also helps in economizing mortar and concrete construction along with the reuse of certain waste materials. This study aimed to utilize pumice in cement mortar at high contents and evaluate its influence on the mechanical and durability properties, as well as microstructure of mortar specimens. For this purpose, different percentages of cement up to 40% were replaced with pumice. A series of tests such as compression strength, flexure strength, porosity, acid attack resistance, and Fourier-transform infrared spectroscopy (FTIR), Thermogravimetric Analysis (TGA), and SEM-EDX analyses were conducted. The results show that the sample C80–P20 (80% cement and 20% pumice) had 9.8% higher compressive strength and 36% lower porosity than the control group after 90 days curing period. The inclusion of pumice led to a higher resistance against acid attack as the control sample severely deteriorated and lost about 30% mass, while the sample C60–P40 lost only 10% mass. The FTIR, TGA and SEM-EDX tests also confirmed the pozzolanic reactivity of pumice thereby, justifying the improved mechanical and durability performance of the samples incorporating pumice. Highlights: High percentage cement replacement with pumice provided adequate strength with good durability properties. Pumice samples had lower porosity than control samples. SEM images showed a compact and denser microstructure of pumice samples. TGA results showed that thermal stability of pumice samples was better than control samples.